Quality of life for patients on oncology treatments in the Kingdom of Saudi Arabia: a systematic review - Abdullah U. Althemery; Rawan Alzahrani; Nura Alajlan; Abdullah M. Alrajhi (Journal of Pharmaceutical Policy and Practice)
Background Cancer cases in the Kingdom of Saudi Arabia (KSA) have tripled in recent years. Quality of Life (QoL) measurements are crucial for healthcare professionals because they reveal important information about how patients respond to drugs and their general health. This study aimed to collect and summarise articles exploring the QoL of patients undergoing oncology treatments in KSA.Methods This systematic review captured articles on the Quality of Life of patients undergoing oncology treatments living in the KSA from 2000–2023. A query was established by adapting (PICOS) guidelines for systematic research. A systematic review accelerator (SRA) was used to organise the search and enable multiple reviewers to conduct and validate the process.Results Twelve articles met the inclusion criteria. Riyadh and Jeddah contributed to all publications. A total of 2,430 patients with cancer were surveyed; 1,377 patients were female (56.67%) with an average age of 51.23 years. Six articles mentioned pharmacological interventions, whereas the remaining articles did not mention which pharmacology had been utilised.Conclusion This systematic review highlights the recent attention given to the patient’s reported outcomes of cancer patients. Further research on rare cancer types is required, particularly for generic instruments.